2014
DOI: 10.1159/000358667
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of a-Lipoic Acid with Keratinocyte Growth Factor on Protecting Alveolar Epithelial Type II Cells of Rat Fetus from Hyperoxia -Induced Injury

Abstract: Aim: To explore the potential mechanism of the synergetic effect of α-lipoic acid with keratinocyte growth factor (KGF) on protecting alveolar epithelial type II cells (ATIICs) from hyperoxia-induced injury. Methods: Primary culture of ATIICs from the Sprague-Dawley rat fetuses was examined under room air and 95% of O2. Various KGF concentrations (0 to 100 ng/mL) and 0.5 mM of α-lipoic were added into the cell culture. Levels of intracellular reactive oxygen species, necrosis, and proliferation of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The well-studied pulmonary toxicity of hyperoxic gas is known to involve apoptotic cell death of alveolar epithelial cells (26), but exposure of the cell line IMR90 to a high oxygen concentration that is often administered to premature neonates (95% O2) did not increase a marker of apoptotic cell death in these fetal human lung fibroblasts (caspase 9, Figure 1). Although the 95% oxygen did cause a very minor increase in necrotic cells (<1% see Table 1), it seems unlikely that this small but statistically significant effect would have physiologic significance.…”
Section: Discussionmentioning
confidence: 96%
“…The well-studied pulmonary toxicity of hyperoxic gas is known to involve apoptotic cell death of alveolar epithelial cells (26), but exposure of the cell line IMR90 to a high oxygen concentration that is often administered to premature neonates (95% O2) did not increase a marker of apoptotic cell death in these fetal human lung fibroblasts (caspase 9, Figure 1). Although the 95% oxygen did cause a very minor increase in necrotic cells (<1% see Table 1), it seems unlikely that this small but statistically significant effect would have physiologic significance.…”
Section: Discussionmentioning
confidence: 96%
“…ROS induce endothelial dysfunction, cardiovascular and renal remodeling, inflammation and fibrosis. Previous studies have shown that AngII is closely associated with fibrosis in multiple organs (4,5). As pulmonary fibrosis results in a severe prognosis for newborns after hyperoxic treatment, AngII-induced ROS are thought to be a factor that should be considered in relation to the formation of pulmonary fibrosis (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, hyperoxia-induced lung injury occurs, which is represented by pulmonary fibrosis. Therefore, neonates continue to require mechanical ventilation and oxygen therapy after their primary diseases have improved (3,4). …”
Section: Introductionmentioning
confidence: 99%
“…Cells were seeded into 6-, 24-, or 96-well cell culture plates overnight. The next day, cells were placed in hyperoxia (80% O 2 , 5% CO 2 ) or normoxic (21% O 2 , 5% CO 2 ) environment as previously described [ 20 , 25 , 26 ]. The concentration of O 2 was monitored in real time with a digital oxygen monitor (Hengaode, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%